Resource utilisation and power relations of community sport clubs in the aftermath of natural disasters. Issue 4 (November 2015) - Filo, Kevin; Cuskelly, Graham; Wicker, Pamela
Highlights: We visited nine community sport clubs (CSCs) impacted by flooding in Queensland. Resource dependence theory is applied as the framework guiding each site visit. Three entities provided resources: volunteers and members, partner organisations and government. The relations between CSCs and resource providers were impacted in different ways. Resource providers exerted power over CSCs through one-way communication and priority. Abstract: Community sport clubs (CSCs) provide a number of benefits to local communities, while confronting challenges with finances and staffing. In Queensland, Australia, these challenges have been compounded by recent natural disasters including widespread flooding that have significantly impacted operations of CSCs. The current research explores the provision of resources to CSCs in the aftermath of flooding events in 2010 and 2011, as well as the influence on power relations between CSCs and resource providers. To address this research purpose, qualitative data were collected across nine site visits (focus groups, interviews) to affected CSCs. The data revealed three resource providers: volunteers and members, partner organisations and government. In addition, the results indicate that relations between CSCs and members and volunteers, partner organisations and government were impacted in different ways. Examples of resource providers wielding power over CSCs due to the provision of resources emerged, along with some evidence of mutual power and dependence and CSCs exerting power over resource providers. The results provide implications for CSC managers to be more proactive in relation to resourcing through developing strategies for network building and improved communication within networks.